Taxonomia de Acilepidopsis, Chrysolaena, Echinocoryne, Stenocephalum e Vernonanthura (Vernonieae, Asteraceae) de Minas Gerais, Brasil - Soares, Polyana Noronha (2012)
Asteraceae is the biggest family within the angiosperms. It is organized in 43 tribes with something about 1600 genera and 23000-30000 species. The tribe Vernonieae has 125 genera and more than 1500 species. It is distributed in America, with a great diversity in the southeast of Brazil, south of Africa, southeast of Asia and in the Pacific. Vernonieae is considered monophyletic, however it is not easy to identify its subtribes because of the size and distribution of the genus Vernonia core. Therefore, based on recent studies Vernonieae was divided in 21 subtribes. The subtribes Mesanthophorinae, Lepidaploinae and Vernoniinae stand out as important because they represent with half of the genera included in the tribe most of the genera segregated from Vernonia s. l. that occur in Brazil. Thus, was developed in this work the taxonomic study for the species of the genera Acilepidopsis H. Rob., Chrysolaena H. Rob., Echinocoryne H. Rob., Stenocephalum Sch. Bip. e Vernonanthura H. Rob. that occurs in Minas Gerais. The morphological descriptions were based on the specimens deposited in brazilian herbaria. However in Minas Gerais state there were found 24 species of Venonanthura, of which three species received new combinations. There were also found seven species of Chrysolaena, four species of Echinocoryne, three species of Stenocephalum and one species of Acilepidopsis. The species Chrysolaena sp. nov. and V. cabralensis were considered endemic to Minas Gerais state.